Hedyotis Diffusa Willd Increase Drugs Accumulation by Regulating Hedgehog Pathway in Drug Resistant Colorectal Cancer Cells - Yiyi JIN; Qiongyu LI; Zijun LAI; Zhaokun YAN; Jianyu FENG; Jiumao LIN (康复学报)
Objective:To explore the effect and underlying mechanism of Hedyotis diffusa Willd (HDW) on drug efflux and regulation of Hedgehog (HH) signaling pathway in human colorectal cancer HCT-8/5-FU cells.Methods:HCT-8/5-FU Cells were treated with different concentrations of ethanol extract of HDW (EEHDW). Cell viability was determined by MTT assay, then the inhibitory rate was calculated to evaluate the effect of EEHDW on cell proliferation. Cell morphology was observed under phase-contrast microscope. Intracellular 5-Fluorouracil (5-FU) and Doxorubicin (ADM) accumulation were analyzed using HPLC and observed by fluorescence microscope, respectively. Western Blot was used to determine the expression of multidrug resistance (MDR) related proteins, such as MRP1, P-gp, LRP, BCRP, and the core proteins of HH signaling pathway, including SHH, SMO, SUFU and Gli-1.Results:After treated with different concentration of EEHDW, proliferation of HCT-8/5-FU cells were inhibited in a dose dependent (P<0.01). Cell density decreased with the increase concentration of EEHDW. Accumulation of intracellular 5-FU and ADM significantly increased in HCT-8/5-FU cells. The expression of MRP1, P-gp, LRP and BCRP decreased markedly, and activation of Hedgehog signaling pathway was significantly inhibited.Conclusion:HDW could inhibit drug efflux of human colorectal cancer HCT-8/5-FU cells and increase the accumulation of 5-FU and ADM by inhibiting the activation of HH signaling pathway, which play a role in reversing the drug resistance of colorectal cancer cells.